2019
DOI: 10.18632/aging.101996
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes in the vasculature of the dermis of the upper lip vermilion

Abstract: Lip redness is unique to humans and creates an important facial impression, but this redness decreases with age. Here, using histological and immunohistological staining of human upper lip vermilion from donors of different ages, we investigated blood vessels in the upper lip dermis and age-dependent histological changes. We found that both total vessel area in the dermis and vessel number in the upper dermis decreased with aging. Moreover, vessel number in the upper dermis correlated positively with developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 23 publications
2
23
1
1
Order By: Relevance
“…Depending on the specific context, they may be aimed at limiting the proliferative and invasive frequency of BCSCs. Although these cells are generally resistant to classical ER-targeted therapies, the data presented supports the idea that ER acts unconventionally in BCSCs, paving the way for the study of new GPR30 [48] or ERβ [28] inhibitors or drugs / peptides that specifically inhibit non-genomic action induced by ERs in BC [25,35]. Some of the main pathways operating in BCSC are shown in Figure 1.…”
Section: Er In Bcscssupporting
confidence: 55%
See 2 more Smart Citations
“…Depending on the specific context, they may be aimed at limiting the proliferative and invasive frequency of BCSCs. Although these cells are generally resistant to classical ER-targeted therapies, the data presented supports the idea that ER acts unconventionally in BCSCs, paving the way for the study of new GPR30 [48] or ERβ [28] inhibitors or drugs / peptides that specifically inhibit non-genomic action induced by ERs in BC [25,35]. Some of the main pathways operating in BCSC are shown in Figure 1.…”
Section: Er In Bcscssupporting
confidence: 55%
“…Two isoforms of ER, ERα and ERβ, are expressed in BC [25][26][27][28], with ERα being the most important hormonal biomarker in this cancer. ERα is expressed in almost 75% of BC, and its presence correlates positively with the response to endocrine therapy [29].…”
Section: Er In Bcscsmentioning
confidence: 99%
See 1 more Smart Citation
“…Results of the study by Gomi T. et al [25] testify to the general deterioration of blood vessels in the upper lip dermis during aging. The authors found that both the area and number of blood vessels in the upper lip dermis decreased with age [25].…”
Section: Fig 3 Schematic Representation Of the Dermis Evolution In mentioning
confidence: 94%
“…Age-related changes are not only limited by structural elements of the entire skin dermis, including the face but also by the vessels located in it [24]. Results of the study by Gomi T. et al [25] testify to the general deterioration of blood vessels in the upper lip dermis during aging. The authors found that both the area and number of blood vessels in the upper lip dermis decreased with age [25].…”
Section: Fig 3 Schematic Representation Of the Dermis Evolution In mentioning
confidence: 97%